Studi Literatur Aktivitas Antimalaria Tanaman Afrika (Vernonia amygdalina Del.) - Nursetia Widia Astuti; Sri Peni Fitrianingsih; Suwendar (Bandung Conference Series: Pharmacy, 2022)
Abstract. Malaria is a public health problem in various parts of the world, because malaria causes death in infants, toddlers, pregnant women and adults and can have an impact on social development. The prevalence of malaria in Indonesia in 2019 was 250,644 cases. Most cases almost occurred in Papua, around 86% with a total of 216,380 cases. The second area with the most malaria cases is East Nusa Tenggara with 12,909 cases and West Papua with 7,079 cases. The use of antimalarial drugs with herbal plants has been used by the community empirically, due to the presence of antimalarial drug resistance, especially in malaria endemic areas. So it is necessary to have antimalarial medicinal plants that can be developed into antimalarial herbal medicines. There are many plants that have antimalarial activity, one of which is the African plant (Vernonia amygdalina Del.). There are many plants that have antimalarial activity, one of which is the African plant (Vernonia amygdalina Del.). The purpose of this literature study was to determine the level of antimalarial activity of African plants and to determine the content of secondary metabolites that are efficacious as antimalarials. The research was conducted using the Systematic Literature Review (SLR) method in reputable journals using the keyword Vernonia amygdalina Del antimalarial. The results of the literature study showed that the African plant parts, namely the leaves from the cyclohexane extract with the maceration method, could inhibit the Plasmodium falciparum parasite with an IC50 value of 4.34 g/ml in the very category and the aqueous extract with the maceration method could inhibit the growth of the Plasmodium berghei parasite with % inhibition. by 70.87% with very active category. African plants contain secondary metabolites from the terpenoid group, namely vernodalol and vernolide with IC50 values ​​<10. Abstrak. Penyakit malaria merupakan masalah kesehatan masyarakat di berbagai belahan dunia, karena penyakit malaria menyebabkan kematian pada bayi, balita, ibu hamil dan orang dewasa juga dapat berdampak pada perkembangan sosial. Prevalensi mengenai penyakit malaria yang terjadi di Indonesia pada tahun 2019 yaitu sebanyak 250.644 kasus. Sebagian kasus hampir terjadi di daerah Papua sekitar 86% dengan jumlah 216.380 kasus. Daerah kedua dengan kasus malaria terbanyak yaitu Nusa Tenggara Timur dengan jumlah kasus sebanyak 12.909 kasus dan Papua Barat dengan jumlah kasus 7.079 kasus. Penggunaan obat antimalaria dengan tanaman herbal telah digunakan oleh masyarakat secara empiris, karena adanya resistensi obat antimalaria terutama didaerah endemik malaria. Sehingga diperlukan adanya tumbuhan obat antimalaria yang dapat dikembangkan menjadi obat herbal antimalaria.Terdapat banyak tanaman yang memiliki aktivitas antimalaria salah satunya adalah tanaman afrika (Vernonia amygdalina Del.). Tujuan dari studi literatur ini adalah untuk mengetahui tingkat aktivitas antimalarial tanaman afrika dan mengetahui kandungan metabolit sekunder yang berkhasiat sebagai antimalaria. Penelitian dilakukan dengan metode Systematic Literatur Review (SLR) pada jurnal bereputasi menggunakan kata kunci Vernonia amygdalina Del. antimalarial. Hasil studi literatur menunjukkan bahwa bagian tanaman afrika yakni daun dari mulai ekstrak sikloheksana dengan metode maserasi dapat menghambat parasit Plasmodium falciparum dengan nilai IC50 sebesar 4,34 µg/ml dengan kategori sangat aktif dan ekstrak air dengan metode maserasi dapat menghambat pertumbuhan parasit Plasmodium berghei dengan %hambatannya sebesar 70,87% dengan kategori sangat aktif. Pada tanaman afrika terkandung metabolit sekunder dari golongan terpenoid yaitu vernodalol dan vernolide dengan nilai IC50<10.